Research progress of cell treatment strategy in Parkinson's disease - Peng, Ying-Long; Chen, Jinwei; Hu, Hengxiao; Liu, Wenxiong; Liang, Weiye; Wang, Jian (Neuroscience Applied, 2024)
Parkinson's disease (PD) is a neurological disorder that often affects middle-aged and elderly people. It is primarily characterized by the degeneration of dopaminergic (DA) neurons in the ventral midbrain. Clinical therapy mostly relies on the holistic approach of pharmaceutical intervention and surgical procedures. Nevertheless, therapies might just alleviate symptoms temporarily and then result in notable adverse consequences, ultimately failing to produce a therapeutic outcome. Stem cells has the benefits of being capable of self-renewal and exhibiting multi-directional differentiation potential. This enables replacement of dysfunctional neurons and reconstruction of neural circuit, offering promise for the treatment of Parkinson's disease. This research examines and evaluates the fundamental principles, effectiveness, benefits, and drawbacks of various stem cell types in the treatment of Parkinson's disease. This review provides a concise summary of many potential processes by which stem cells might be effective in treating Parkinson's disease. The aim is to support ongoing research and clinical trials focused on using stem cells for the treatment of Parkinson's disease.